A Catalogue of metopiinae ( hymenoptera: ichneumonidae) from Malaysia. - Nahla, M.A.I; Idris, A.B (Pusat Sistematik Serangga ,UKM, 2010)
There were 11 recorded genera of metopiinae from Malaysia namely the acerataspis, chorinaeus, colpotorchia,drepanoctonus exochus hypsicera, macromalon,metopius,periope, triclistus and trieces. The only recrded species were the exochus appendiculatus cameron,1992, from Cameron Highland (Pahang),hypsicera cavicola cushman, 1930, from Batu Caves (Selangor) and metopius dissectorius lar morely, 1912 from Sabah and Penang.